ANALISIS PERAN SEKOLAH SEBAGAI SISTEM KELEMBAGAAN DALAM PENANAMAN NILAI TOLERANSI BERAGAMA DI SMAN 6 MATARAM - Susi Lestari; Bagdawansyah Alqadri; Nurlatifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted due to the complex problems with Indonesian society, which is pluralistic with diverse religions, cultures, and ethnicities that have the potential to cause social conflict if not properly managed. The study aims to describe the role of schools as institutional systems in instilling religious tolerance values from the ground up at SMA Negeri 6 Mataram. The research employed a qualitative approach with data collection techniques such as interviews, observations, and documentation, which were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings show that the cultivation of religious tolerance at SMA Negeri 6 Mataram is carried out through four main aspects: school policies based on tolerance, strengthening an inclusive and harmonious school culture, providing equal worship facilities for all religions, and implementing interfaith programs such as spiritual camps, social service activities, and interfaith harmony discussions. The process is not always easy, as challenges faced by the school include uneven student understanding of the meaning of tolerance, with some extreme views influenced by various factors such as social media and peer interactions. As an institutional system, the school plays an important role in building religious tolerance through integrated policies, culture, facilities, and religious programs. This study is expected to provide theoretical contributions to the development of multicultural education and practical benefits for schools, teachers, and students in creating a peaceful and inclusive learning environment.